Editor's Choice – Endovascular Aneurysm Repair in High Risk Patients: A Systematic Review and Meta-Analysis. (November 2022) - Kontopodis, Nikolaos; Galanakis, Nikolaos; Charalambous, Stavros; Matsagkas, Miltiadis; Giannoukas, Athanasios D.; Tsetis, Dimitrios; Ioannou, Christos V.; Antoniou, George A.
Abstract : Objective: To investigate outcomes of endovascular aneurysm repair (EVAR) in high risk patients. Methods: Bibliographic sources (MEDLINE, EMBASE, CINAHL, and CENTRAL) were searched using combinations of thesaurus and free text terms. The review protocol was registered in PROSPERO (CRD42021287207) and reported according to PRISMA 2020. Pooled estimates were calculated using odds ratio (OR) or hazard ratio (HR) and 95% confidence interval (CI) applying the Mantel–Haenszel or inverse variance method. EVAR peri-operative mortality in high risk patients over time was examined with mixed effects meta-regression. The GRADE framework was used to rate the certainty of evidence. Results: The pooled peri-operative mortality in 18 416 high risk patients who underwent EVAR was 3% (95% CI 2.3 – 4%) and has significantly reduced over time (year of publication p = .003; median study point p = .023). The peri-operative mortality was significantly lower in high risk patients treated with EVAR compared with open repair (OR 0.64; 95% CI 0.45 – 0.92), but no significant difference was found in overall (HR 1.06; 95% CI 0.76 – 1.49) or aneurysm related mortality (HR 0.57; 95% CI 0.21 – 1.55). No significant difference was found in overall mortality between high risk patients treated with EVAR vs. no intervention (HR 0.42; 95% CI 0.14 – 1.26), but the aneurysm related mortality was significantly lower in the former (HR 0.30; 95% CI 0.14 – 0.63). The peri-operative mortality was higher in high risk than normal risk patients treated with EVAR (OR 2.33; 95% CI 1.75 – 3.10), as was the overall mortality (HR 3.50; 95% CI 2.55 – 4.80). The certainty of evidence was very low for EVAR vs. open surgery or no intervention and low for high vs. normal risk patients. Conclusion: The EVAR peri-operative mortality in high risk patients has improved over time. Even though the aneurysm related mortality of EVAR is lower compared with no intervention, EVAR may confer no overall survival benefit.